Alkoholické epilepsie - Skopková, H (Ceskoslovenska psychiatrie, 1991)
The author analyzes a group of 83 patients with epileptic fits which developed in conjunction with drinking. She compares them with a group investigated 12 years previously. She mentions also some catamnestic findings pertaining to the group. The author describes signs of alcoholic epilepsy which include age above 30 years, in particular a 10-year history of drinking, altered reactivity of the brain to alcohol, high alcohol tolerance, development of fits without an aura and how frequency of fits. The author reflects on the causes of alcoholic epilepsy and emphasizes the basic therapy--strict abstinence. She proved also an increase of somatic and neurological damage and the number of deaths in subjects with the diagnosis of alcoholic epilepsy.
Keywords: Epilepsy; Adult; dospělí; epilepsie; Alcoholism; Humans; lidé; alkoholismus